Board Characteristics and Risk Disclosure Quality by Integrated Reporters : Evidence from Indian Banks - Matta, Rahul; Kochhar, Khyati; Mohapatra, Amiya Kumar; Mohanty, Debasis (Prabandhan: Indian Journal of Management, 2022)
This study aimed to analyze the influence of board characteristics on the quality of risk disclosures in integrated annual reports of banks in India. Integrated reports support organizations in controlling risks, identifying opportunities, connecting risks with business policies, developing business models, and contributing to the value creation process. In February 2017, the Securities and Exchange Board of India (SEBI) recommended the adoption of an integrated reporting (IR) framework by the top 500 companies in India on a voluntary basis from 2017–18. Considering the relevance of integrated reporting and its underlying benefits to various stakeholders, banks have primarily adopted the IR framework and started publishing their annual reports in line with the IR principles. Using content analysis on the sample of 30 banks listed on the National Stock Exchange (NSE) in India, the efficacy of risk disclosures, the outlook orientation (past, present, and future), approaches to risk (positive, neutral, and negative) were investigated, and the influence of attributes of board of directors on the quality of risk disclosure was examined. On examining 4,183 sentences concerning risk disclosures by Indian banks, the results showed a positive relationship between board size, diversity, independence, meetings, and education background in accounting/finance with risk disclosure quality (RDQ). Also, it was found that integrated reporters tended to disclose more risks and suggested ways to mitigate those risks compared to non-adopters.